Protecting assets and enhancing welfare: The potential of gender-differentiated group-based approaches - Rakib, Muntaha; Matz, Julia Anna (International Food Policy Research Institute, 2014)
This policy note summarizes the main insights from a study on the factors associated with men’s and women’s participation in different types of groups and investigates the relationship between social capital and household and individual welfare among agricultural households in Bangladesh. The study contributes to existing research both by assessing how social capital impacts on the welfare of men and women differently and by considering the extent to which gender-differentiated group-based forces play a role in this.